2020
DOI: 10.1002/jbmr.4490
|View full text |Cite
|
Sign up to set email alerts
|

Novel Pathogenetic Variants in PTHLH and TRPS1 Genes Causing Syndromic Brachydactyly

Abstract: Skeletal disorders, including both isolated and syndromic brachydactyly type E, derive from genetic defects affecting the fine tuning of the network of pathways involved in skeletogenesis and growth-plate development. Alterations of different genes of this network may result in overlapping phenotypes, as exemplified by disorders due to the impairment of the parathyroid hormone/parathyroid hormone-related protein pathway, and obtaining a correct diagnosis is sometimes challenging without a genetic confirmation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
(66 reference statements)
1
6
0
Order By: Relevance
“…Meanwhile, the patient II2 only had short fourth metacarpals in both hands. Our gathered data also showed that all the c.146dupA mutation carried individuals had short stature (−2 SD), including II2, III6, III16, III17, IV11, but the unaffected members in the pedigree had normal height, which was consistent with the previous literatures manifested that most affected individuals with PTHLH mutations had short stature (Elli et al., 2021 ; Klopocki et al., 2010 ; Thomas‐Teinturier et al., 2016 ). The short height of the affected individuals was probably caused by the premature closure of growth plate (Karaplis et al., 1994 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Meanwhile, the patient II2 only had short fourth metacarpals in both hands. Our gathered data also showed that all the c.146dupA mutation carried individuals had short stature (−2 SD), including II2, III6, III16, III17, IV11, but the unaffected members in the pedigree had normal height, which was consistent with the previous literatures manifested that most affected individuals with PTHLH mutations had short stature (Elli et al., 2021 ; Klopocki et al., 2010 ; Thomas‐Teinturier et al., 2016 ). The short height of the affected individuals was probably caused by the premature closure of growth plate (Karaplis et al., 1994 ).…”
Section: Discussionsupporting
confidence: 91%
“…( 2010 ) identified p.L44P, p.L60P, p.K120*, and p.*178 W firstly in 2010 and proposed that loss‐of‐function mutations in PTHLH caused BDE with short stature. Subsequently, p.L15R, p.R56*, p.N87Tfs*18, p.R57*, p.Met1?, and p.E100Gfs*5 mutation in exons were identified (Bae et al., 2018 ; Elli et al., 2021 ; Jamsheer et al., 2016 ; Pereda et al., 2017 ; Wang et al., 2015 ). Additionally, two intragenetic novel alterations involving intron (c.101 + 3delAAGT, c.47_101 + 73del128) were also identified (Thomas‐Teinturier et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, twelve PTHLH mutations ( Bae et al, 2018 ; Elli et al, 2022 ; Fu et al, 2019 ; Jamsheer et al, 2016 ; Klopocki et al, 2010 ; Pereda et al, 2017 ; Reyes et al, 2019 ; Thomas-Teinturier et al, 2016 ; Wang et al, 2015 ), two families with PTHLH deletions ( Huang et al, 2019 ; Klopocki et al, 2010 ) and two families with balanced translocations leading to repression of PTHLH ( Maass et al, 2012 ; Maass et al, 2010 ) causing BDE have been reported to our knowledge (see Table 2 ). In 2010, Klopocki et al reported the first 5 unrelated families with gene defects in PTHLH .…”
Section: Discussionmentioning
confidence: 99%
“…TRPS I is caused by a variety of mutations in the TRPS1 gene, including a gene deletion [ 45 ]. A recent study described a novel genetic variant in the TRPS1 gene that causes syndromic brachydactyly with defects in skeletal formation and growth plate development [ 46 ]. In addition, GWAS studies have found an association of SNPs in the TRPS1 gene with femoral neck bone mineral density [ 47 ] and estimated heel bone mineral density, indicating the importance of the gene in bone remodelling [ 48 ].…”
Section: Cnvs In Causal Genes Directly Affect Development Of Osteopor...mentioning
confidence: 99%